1981
DOI: 10.1073/pnas.78.4.2368
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of the initial stage of endochondral ossification: in vitro sequential culture of growth cartilage cells and bone marrow cells.

Abstract: Growth cartilage cells were isolated from the ribs of young rats and cultured at high cell density in Ham's F-12 medium supplemented with 10% fetal calf serum. During 7 days, glycosaminoglycans and proteoglycans were actively synthesized and secreted, forming a metachromatic matrix. When cultured together with growth cartilage cells precultured and biosynthetically prelabeled with 35SO42-in their glycosaminoglycans, bone marrow cells caused release of 35S-labeled material into the culture medium. Glycosaminogl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
22
1

Year Published

1988
1988
2001
2001

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 18 publications
2
22
1
Order By: Relevance
“…In some experiments, a cell suspension (20 x 104 cells in 0.1 ml of medium A) was transferred into stainless steel Penicylinders (inside diameter, 6 mm; Kamei, Osaka, Japan) placed in the center of 35-mm plastic tissue culture dishes. These cells were incubated for about 24 hr at 370C under 5% CO2 in air until the cells became attached to the substrate (12). The Penicylinders were then removed, and the cultures were exposed to 1 ml of medium A. Alternatively, cells were seeded at a low density (8 x 104 cells in 1 ml of medium A per 35-mm plastic tissue culture dish).…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In some experiments, a cell suspension (20 x 104 cells in 0.1 ml of medium A) was transferred into stainless steel Penicylinders (inside diameter, 6 mm; Kamei, Osaka, Japan) placed in the center of 35-mm plastic tissue culture dishes. These cells were incubated for about 24 hr at 370C under 5% CO2 in air until the cells became attached to the substrate (12). The Penicylinders were then removed, and the cultures were exposed to 1 ml of medium A. Alternatively, cells were seeded at a low density (8 x 104 cells in 1 ml of medium A per 35-mm plastic tissue culture dish).…”
Section: Methodsmentioning
confidence: 99%
“…Cultures maintained for [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22] days in centrifuge tubes were washed three times with methioninefree MEM and then exposed for 3 hr to 10 ,Ci of L-…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…One of the distinguishing features of enlarging chondrocytes within the hypertrophic zone is the production of matrix vesicles (Anderson 1995). Matrix vesicles, small extracellular membranous particles containing alkaline phosphatase and ATPase (Boyan et al 1989, Matsuzawa & Anderson 1971, have been shown to dock at the side of polarised cytoplasmic membranes of chondrocytes (Glaser & Conrad 1981, Suzuki et al 1981 and osteoblasts (Boyan et al 1989, Sudo et al 1983 where they then bud from the membrane and are subsequently expelled into the extracellular matrix. The restriction of matrix vesicle deposition defines the spatial regulation of the process.…”
Section: Resultsmentioning
confidence: 99%